(untitled) (Contemporary Journal of Social Science Review, 2025)
The aim of this study was to examine how school leaders in Punjab, Pakistan, show authentic leadership traits and apply principles from The Seven Habits of Highly Effective People (Covey), to make a comparison and contrast the two styles in the educational leadership context. The objectives of the study were: (1) to compare the relationship between the dimensions of authentic leadership styles of educational leaders and the seven habits of highly effective people at the level of independence, the level of interdependence, and the level of continuous improvement. The population of the study was all (42) Districts of the Province of Punjab, all (8087) Secondary Schools in the Province of Punjab, all (4178) Headmasters of Secondary Schools of the Province of Punjab, all (3909) Headmistresses of Secondary Schools of the Province of Punjab, and all (45424) Secondary School Teachers of Public Secondary School of Punjab. A multistage purposive stratified sampling technique was used to select the sample for the study. The population of the study comprised various subgroups or strata, i.e., Countryside and urban, male and female, so a stratified purposive sampling technique was used to select the sample. Data was collected by means of four Questionnaires, two of which were designed on a five-point Likert scale and two on a six-point Likert scale related to the seven habits of highly effective and authentic leadership style. Self-reported authentic leadership styles and views about secondary school teachers were analyzed by considering the Seven Habits of Highly Effective People as defined by Covey. The initial stage was “Level of Independence” where educational leaders were measured by using the first three habits: “Be Proactive”, “Begin with the end in mind”, and “Put first things first”. Those educational leaders who were successful at this Level were considered to measure “the level of interdependence” and usefulness at the Second Stage by means of the next three habits: “Think win/win”, “Seek first to understand then to be understood”, and “Synergize”. Those educational leaders who remained effective at the Second Level were considered to find out the level of Continuous improvement by using the habit “Sharpen the Saw”. The study highlights significant similarities between the Seven Habits of Highly Effective People and authentic leadership practices. Specifically, the habits of interdependence and continuous development predict leadership effectiveness, suggesting that these habits are central to the authentic leadership style of school heads. The findings also show that female heads and in-charge heads tend to score higher in continuous development, while urban heads show higher levels of independence compared to their rural counterparts The main findings of the study were that the prevailing leadership style of secondary school leaders in the Punjab Education Department was reasonable, but not up to global standards. The final recommendations were made to offer clear strategies for the selection of the leaders, and to establish a specific cell to inculcate and enhance the seven habits of highly effective people among the school leaders, therefore meeting the quality education and global market. The first dimension of AL self-awareness is integrated habits, such as sharpening the saw and being proactive.